2014
DOI: 10.1021/ie404266k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biosorptive Remediation of Hexavalent Chromium Using Chemotailored Biomass of a Novel Soil Isolate Bacillus aryabhattai ITBHU02: Process Variables Optimization through Artificial Neural Network Linked Genetic Algorithm

Abstract: A modified biomass of a novel bacterium, Bacillus aryabhattai ITBHU02, was investigated for the removal of hexavalent chromium [Cr­(VI)] from water. It was found that modification of the biomass had an improved 28.2% higher Cr­(VI) removal and 9.4 mg/g greater uptake capacity as compared to unmodified biomass. At ANN-GA optimized condition of parameters, namely, pH 2.61, biomass dose of 2.8 g/L, temperature of 44 °C, and initial Cr­(VI) concentration of 112 mg/L, the maximum uptake capacity of biomass was achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…The Cr­(VI) is more water-soluble and easily enters into living cells. Therefore, it is more hazardous than Cr­(III) . Cr­(VI) is carcinogenic and mutagenic to human health and also affects other aquatic life forms of the ecosystem. , The remediation of Cr­(VI) from water is a big challenge because it is found as negative ions in water which poorly interact with the sediment and soil particles in the environment …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cr­(VI) is more water-soluble and easily enters into living cells. Therefore, it is more hazardous than Cr­(III) . Cr­(VI) is carcinogenic and mutagenic to human health and also affects other aquatic life forms of the ecosystem. , The remediation of Cr­(VI) from water is a big challenge because it is found as negative ions in water which poorly interact with the sediment and soil particles in the environment …”
Section: Introductionmentioning
confidence: 99%
“…Various methods such as chemical precipitation, ion exchange, membrane separation, and adsorption have been established for the removal of Cr­(VI) from water. , Among these, adsorption is an avenue to develop an economic and efficient method with no risk of secondary pollution. , Various adsorbents including clays, activated carbon, waste biomass, inorganic silicates, and polymer nanofiber have been used as adsorbents for the remediation of Cr­(VI). Nevertheless, most of the reported adsorbents are suffering for practical use due to either low adsorption capacity or no understanding of the kinetics, isotherms, and thermodynamics of the adsorption process.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the rate limiting step of the sorption was accompanied by a chemisorption process. This fact suggested that the Pb(II) ions might undergo either complexation or coordination through sharing or exchanging electrons between Pb(II) ions and hydroxyl groups of hematite nanorods …”
Section: Resultsmentioning
confidence: 99%
“…The optimum solution for the screened process was achieved by recapitulating the optimized process conditions for different GA input variable conditions. GA inputs of the previous literature reported that the solution must be a global optimal solution (Verma et al, 2014). The best fitness plot accessed during the analysis after 50 generations explains the steady progression of the results with respect to the optimal solution.…”
Section: Genetic Algorithmmentioning
confidence: 90%